Analysis of the Implementation of E-SPTPD (Electronic Based Local Tax Notification Letter) in Financial Management and Local Taxes in Gianyar Regency - Ni Wayan Wirati; Nyoman Diah Utari Dewi; Anak Agung Gede Rai (Departement of Mathematics Education, 2024)
The implementation of e-SPTPD (Electronic Based Local Tax Return) aims to improve the efficiency, transparency, and accountability of local financial and tax management. This study evaluates the implementation of e-SPTPD in Gianyar Regency, focusing on taxpayer compliance, taxpayer satisfaction factors, and constraints and challenges faced. The method used is a literature review by analyzing various relevant studies. The results showed a positive impact of e-SPTPD on taxpayer compliance, especially in the ease of online tax reporting and payment. Factors such as performance expectations, social influence, and user attitudes towards technology affect taxpayer satisfaction. However, obstacles such as low taxpayer knowledge and uneven internet infrastructure need to be overcome. Recommendations include improving socialization, education, infrastructure, technical support, and developing a more user-friendly system. By overcoming these obstacles, e-SPTPD is expected to function more effectively and efficiently, increasing taxpayer compliance and satisfaction